TFRC–RNA interactions show the regulation of gene expression and alternative splicing associated with IgAN in human renal tubule mesangial cells - Li, Jian-Si; Chen, Xiao; Luo, Ailing; Chen, Dong (Frontiers in Genetics, 2023)
IgA nephropathy (IgAN) is the most common primary glomerular disease (PGD) which could progress to renal failure and is characterized by aberrant IgA immune complex deposition. Transferrin receptor1 (TFRC), an IgA receptor, is a potential RNA binding protein (RBP) which regulates expression of genes positively associated with the cell cycle and proliferation and is involved in IgAN. Molecular mechanisms by which TFRC affects IgAN development remain unclear. In this study, TFRC was overexpressed in human renal tubular mesangial cells (HRMCs) and RNA-sequencing (RNA-seq) and improved RNA immunoprecipitation sequencing (iRIP-seq) were performed. The aim was to identify potential RNA targets of TFRC at transcriptional and alternative splicing (AS) levels. TFRC-regulated AS genes were enriched in mRNA splicing and DNA repair, consistent with global changes due to TFRC overexpression (TFRC-OE). Expression of TFRC-regulated genes potentially associated with IgAN, including CENPH, FOXM1, KIFC1, TOP2A, FABP4, ID1, KIF20A, ATF3, H19, IRF7, and H1-2, and with AS, CYGB, MCM7 and HNRNPH1, were investigated by RT-qPCR and iRIP-seq data analyzed to identify TFRC-bound RNA targets. RCC1 and RPPH1 were found to be TFRC-bound RNA targets involved in cell proliferation. In conclusion, molecular TFRC targets were identified in HRMCs and TFRC found to regulate gene transcription and AS. TFRC is considered to have potential as a clinical therapeutic target.